A dynamic theory of electoral competition. Issue 2 (2nd June 2014) - Battaglini, Marco
<x xml:space="preserve">Abstract</x> We present a dynamic theory of electoral competition to study the determinants of fiscal policy. In each period, two parties choose electoral platforms to maximize the expected number of elected representatives. The platforms include public expenditure, redistributive transfers, the tax rate, and the level of public debt. Voters cast their vote after seeing the platforms and elect representatives according to a majoritarian winner take all system. The level of debt, by affecting the budget constraint in future periods, creates a strategic linkage between electoral cycles. We characterize the Markov equilibrium of this game when public debt is the state variable and study how Pareto efficiency depends on the electoral rule and the underlying fundamentals of the economy.